Pendidikan Islam Pada Masa Awal di Indonesia - Muhammad Agung Raharjo; Muhammad Yahdi (STIKes Ibnu Sina Ajibarang, 2025)
The history of the spread of Islamic education in the early days in Indonesia is an integral part of the process of Islamization of the archipelago that has been going on since the 13th century. Islamic education not only functions as a means of spreading religion, but also as a medium for forming the social, cultural, and intellectual character of the community. This process is carried out through various channels, including the role of ulama, Islamic boarding schools, surau, and mosques as centers of education. This study aims to analyze the dynamics of the process of spreading Islamic education in the early days, by examining various supporting factors such as trade routes, cultural acculturation, and the involvement of local communities. A literature review approach is used to explore relevant literature, including historical manuscripts, current research, and other academic documents. The findings show that the success of Islamic education in the early days cannot be separated from the strategy of cultural adaptation, teaching based on local traditions, and the support of the diaspora ulama community in various regions. Previous research, such as that conducted by Azra, emphasized the importance of the ulama network in Southeast Asia and the contribution of traditional educational institutions in building an inclusive and sustainable Islamic education system. The conclusion of this study confirms that Islamic education in the early days in Indonesia played a significant role in shaping the social structure and religious identity of the community. To strengthen its relevance, further study is needed on the transformation of the early Islamic education system and its implications for the challenges of modern education in Indonesia.